Research Progress on Gene Editing Based on Nano-Drug Delivery Vectors for Tumor Therapy - Xi, Shiwen; Yang, Yong-Guang; Suo, Jian; Sun, Tianmeng (Frontiers in Bioengineering and Biotechnology, 2022)
Malignant tumors pose a serious threat to human health and have high fatality rates. Conven-tional clinical anti-tumor treatment is mainly based on traditional surgery, chemotherapy, radi-otherapy, and interventional therapy, and even though these treatment methods are constantly updated, a satisfactory efficacy is yet to be obtained. Therefore, research on novel cancer treatments is being actively pursued. We review the classification of gene therapies of malignant tumors and its advantages, as well as the development of gene-editing techniques. We further reveal the nano-drug delivery carrier effect in improving the efficiency of gene editing. Finally, we summarize the progress in recent years of gene editing techniques based on nano-drug delivery carriers in the treatment of various malignant tumors, and analyze the prospects of the technique and its restricting factors.